Herpes simplex virus type 1 Angelotti and a defective viral genotype: analysis of genome structures and genetic relatedness by DNA-DNA reassociation kinetics. - Ott, A (1979)
DNA-DNA reassociation kinetics of herpes simplex virus type 1 Angelotti DNA and a class of defective viral DNA revealed that the viral standard genome has a total sequence complexity of about 93 X 10(6) daltons and that a portion of 11 X 10(6) daltons occurs twice on the viral genome. These results agree with structural features of herpes simplex virus type 1 DNA derived from electron microscopic studies and restriction enzyme analyses by several investigators. The defective viral DNA (molecular weight, about 97 X 10(6)) displays a sequence complexity of about 11 X 10(6) daltons, suggesting that the molecule is built up by repetitions of standard DNA sequences comprising about 15,000 base pairs. A 2 X 10(6)-dalton portion of these sequences maps in the redundant region and a 9 X 10(6)-dalton portion maps in the unique part of the standard herpes simplex virus type 1 Angelotti DNA, as could be shown by reassociation of viral standard DNA in the presence of defective DNA and vice versa. No cellular DNA sequences could be detected in defective DNA. A 12% molar fraction of the defective DNA consists of highly repetitive sequences of about 350 to 500 base pairs in length.